Mikro-Irigasi Cerdas dengan Sprinkler Menggunakan Fuzzy Logic Pada Lahan Terbatas Untuk Pertanian 4.0 - Abdul Haris; Hengki Sikumbang; L.M Syahrul Anwar (Faktor Exacta, 2021)
Most irrigation systems in Indonesia use surface irrigation systems or conventional irrigation, which are still heavily influenced by Earth's gravity, making it very difficult to manage and monitor. while current technological developments are almost evenly distributed throughout Indonesia with an already very good internet network, so that it can be used to support agricultural systems 4.0. In this study, researchers used intelligent computing technology on micro irrigation with Fuzzy Logic algorithm and Sugeno inference to decide when irrigation water is distributed to sprinkler irrigation systems based on a predetermined range value, then the results are evaluated to see the accuracy of the model that has been made before testing in the actual environment. The purpose of this research is to produce smart micro irrigation technology that can be used on limited land and lack of water so that it can help facilitate the work of farmers.